ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI DAN PEMILIHAN TEMPAT BERZAKAT DAN BERINFAK - Irfan Syauqi Beik; Izzatul Mabniyyah Alhasanah (Faculty of Economics, Universitas Islam Indonesia, 2012)
Brebes is one of the region that has high rate of poverty on national level. In the same time, however, Brebes is also the forth highest of Regional GDP in Central Java. One of instrument that is expected to reduce the poverty rate and income disparity is zakah. This research is aim to analyse factors affecting participation rate of society for paying zakah, charity, and choosing its payment place in Brebes Region. A questionare was distributed to 100 respondents and then analyzed by using discriminant factor. The result shows that factors affecting participation rate for paying zakah are believe, altruism, appreciation, organization, and income. In addition, factors affecting participation rate for paying charity are believe, altruism, satisfaction, education level, and frequency for charity. Meanwhile, education and organization on Zakah Management (OPZ) affect the choice of payment place for zakah.